Classmates With Disabilities and Students' Noncognitive Outcomes. (March 2014) - Gottfried, Michael A.
The increasing trend of placing students with disabilities in general education classrooms has raised questions among researchers, policymakers, practitioners, and parents about classmate peer effects on all students. However, little is known about the peer effects of classmates with disabilities on the outcomes of other students in the classroom; no research has evaluated these peer effects on other students' noncognitive outcomes though they are highly predictive of schooling and lifelong success. The purpose of this study is to fill this research gap by using quasi-experimental methods on a nationally representative data set (i.e., Early Childhood Longitudinal Study–Kindergarten Class) of elementary school students to examine the peer effects of classmates with disabilities on five noncognitive scales for classmates without disabilities. The findings indicate that students with a greater number of classmates with disabilities have higher externalizing and internalizing behavioral problems and lower frequencies of self-control, approaches to learning, and interpersonal skills. The findings are differentiated by disability category of a student's classmates and are moderated by individual and contextual factors. Implications for policy and practice are addressed.